Hierarchical multi-component nanofiber separators for lithium polysulfide capture in lithium–sulfur batteries: an experimental and molecular modeling study. Issue 35 (19th August 2016) - Zhu, Jiadeng; Yildirim, Erol; Aly, Karim; Shen, Jialong; Chen, Chen; Lu, Yao; Jiang, Mengjin; Kim, David; Tonelli, Alan E.; Pasquinelli, Melissa A.; Bradford, Philip D.; Zhang, Xiangwu
Abstract : A multi-functional nanofiber membrane significantly improves the overall performance of Li–S batteries. Abstract : Sulfur (S) has been considered as a promising cathode candidate for lithium batteries due to its high theoretical specific capacity and energy density. However, the low active material utilization, severe capacity fading, and short lifespan of the resultant lithium–sulfur (Li–S) batteries have greatly hindered their practicality. In this work, a multi-functional polyacrylonitrile/silica nanofiber membrane with an integral ultralight and thin multi-walled carbon nanotube sheet is presented and it provides a new approach to significantly improve the overall electrochemical performance of Li–S batteries. The experimental results are in agreement with molecular modeling studies based on density functional theory and Monte Carlo simulations. Remarkably, this design is favorable for the fast diffusion of both lithium ions and electrons and the mitigation of the diffusion of polysulfides. As a consequence, a high reversible capacity of 741 mA h g −1 at 0.2C after 100 cycles with excellent cyclability and high-rate performance (627 mA h g −1 at 1C) are achieved even with a high sulfur loading of 70 wt% in the cathode, revealing its great potential for energy storage applications. Moreover, a capacity of 426 mA h g −1 is retained after 300 cycles at a high current density of 2C. These results represent a major step forward in the progress of Li–S battery technologies.